The politics of race, culture and gender in three South Asian novels : the grass is singing, the lying days and disgrace - Khan, Sadia Ambreen (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2015.